2021
DOI: 10.1172/jci.insight.146082
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal delivery of a synthetic DNA vaccine protects macaques from Middle East respiratory syndrome coronavirus

Abstract: Emerging coronaviruses from zoonotic reservoirs, including severe acute respiratory syndrome coronavirus (SARS-CoV), Middle East respiratory syndrome coronavirus (MERS-CoV), and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), have been associated with human-to-human transmission and significant morbidity and mortality. Here, we study both intradermal and intramuscular 2-dose delivery regimens of an advanced synthetic DNA vaccine candidate encoding a full-length MERS-CoV spike (S) protein, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…An important feature of the SARS-CoV-2 DNA vaccine is its ability to induce robust cellular as well as humoral immune responses (for reviews see [14][15][16][17][18][19][20]). In contrast to mRNA vaccines that induce robust antibody responses and low T cell responses, several clinical trials have shown that IM-as well as intradermal (ID)-delivered DNA vaccines [12,[56][57][58][59][60] are able to induce both humoral and cellular responses and that the latter is a critical component to maintain durable antibody responses exerted by CD4 + T help. Although the underlying mechanism explaining the difference in immunity induced by DNA versus mRNA vaccines is not clear, the ability to induce T cell responses is important not only for antibody development but also as a second line of defense in protection from spreading infection and disease development.…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…An important feature of the SARS-CoV-2 DNA vaccine is its ability to induce robust cellular as well as humoral immune responses (for reviews see [14][15][16][17][18][19][20]). In contrast to mRNA vaccines that induce robust antibody responses and low T cell responses, several clinical trials have shown that IM-as well as intradermal (ID)-delivered DNA vaccines [12,[56][57][58][59][60] are able to induce both humoral and cellular responses and that the latter is a critical component to maintain durable antibody responses exerted by CD4 + T help. Although the underlying mechanism explaining the difference in immunity induced by DNA versus mRNA vaccines is not clear, the ability to induce T cell responses is important not only for antibody development but also as a second line of defense in protection from spreading infection and disease development.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Our overall experience with DNA vaccines has been that they provide superior cellular immunity in numbers and duration, and the hypothesis to test is that it may be of benefit for the establishment of long-term protective immunity. On the other hand, delivery of DNA via the ID and IM routes in clinical trials has shown the potency of the vaccine platform [12, [56][57][58][59][60]. The combination of DNA with protein delivered simultaneously via the IM route in the same anatomical site further advances the nucleic acid vaccine platform and increases the simultaneous induction of maximal humoral and cellular immune responses.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Furthermore, it protected the mice from lethal challenges by wild-type MERS-CoV, as evidenced by the absence of mortality, body weight loss, and viral detection in various tissues such as nasal turbinates, brains, lungs, and kidneys. Multiple candidate MERS-CoV vaccines have been evaluated for their efficacy in K18-hDPP4 mice [ 32 , 33 , 34 , 35 , 36 ]. In one study, robust neutralizing antibodies were induced in mice and non-human primates immunized with a DNA vector encoding the S gene of MERS-CoV, along with the expressed S1 protein of MERS-CoV [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunized mice lacking the type I interferon receptor (CD46Ge mice) exhibited a strong induction of both MV and MERS-CoV neutralizing antibodies, and they were protected from MERS-CoV challenges without developing pneumonia in their lungs. Rhesus macaques immunized with a synthetic DNA vaccine encoding the S gene of MERS-CoV displayed reduced clinical symptoms, viral loads, and pathological signs in their lungs compared to control animals [ 34 ]. Mice that received intranasal immunization with recombinant parainfluenza virus 5 expressing the S gene of MERS-CoV were also protected from fatal MERS-CoV infections [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, many vaccine candidates against SARS-CoV-2 using the intradermal route (i.d.) have shown promising results, either on laboratory tests on different animal models [5][6][7][8], or in development with clinical trials [9,10]. The i.d.…”
Section: Introductionmentioning
confidence: 99%